A Multi-Dimensional Study on Rashtriya Madhyamik Shiksha Abhiyan (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Universalisation of Secondary Education is the prime concern today before the first world countries like USA, England, Germany and even Denmark. A research study report shows that by 2018, 63% of all US jobs will require education beyond high school. Yet, nearly half of the US work force-about 88 million of 188 million adults aged 18 to 64-has only a high school education or less, and/or low English proficiency. The developing counties are facing similar challenges before them